Computational methods and experimental measurements XV - Carlomagno, G. M.; Brebbia, C. A.; Wessex Institute of Technology; International Conference on Computational Methods and Experimental Measurements 2011 : New Forest, England, Forest). (Southampton : WIT Press, 2011)
Containing edited versions of most of the papers presented at the Fifteenth International Conference on Computational Methods and Experimental Measurements, this book reviews the latest work on these two approaches, and the interaction between them.
Includes bibliographical references and index.
Keywords: Engineering mathematics -- Congresses; Measurement -- Congresses; Engineering -- Data processing -- Congresses